(untitled) (Research, Society and Development, 2020)
Science teaching stimulates students’ questioning and logical reasoning, allowing them to develop citizens capable of facing and solving contemporary obstacles. In addition, this area of knowledge is relevant to students in the final years of elementary school, for collaborating with the understanding of mechanisms that occur in their daily lives. In view of this, this article aimed to present a systematic review of the literature on the subjects of teaching science, science in the ninth year of the final grades and training of science teachers, in works published in the period from 2015 to 2019. In order to identify research contributions related to these issues. In this perspective, the survey was carried out on the CAPES Periódicos Portal, considering that it is considered one of the main virtual resources for academic research. 10 papers were found referring to the descriptors. The results obtained showed the absence of research associated with the analyzed themes, contributing to the relevance of studies of this nature in the academic environment. Therefore, we highlight the need for carrying out new studies in this area, with the aim of expanding knowledge regarding the teaching of Science in the final years of Elementary School.